Dinamika Ruang Publik dan Demokrasi di Era New Media - Saidaturrahmah, Saidaturrahmah; Kholil, Syukur (Ameena Journal, 2023)
The potential of internet users, especially on social media, in Indonesia is substantial. The large number of users has resulted in a significant potential for national turmoil. Furthermore, the emergence of various elements in society that are intolerant and spread hoaxes adds to the national turmoil on social media, thereby misusing the meaning of democracy. This situation has prompted the government to take steps to address the country's divisions. At certain moments, the government takes actions to restrict the internet with the aim of maintaining national stability. These actions receive varied responses, both positive and negative. Based on these various factors, this research aims to examine the role of new media as a public space in responding to the genuine meaning of democracy. The theory employed is Jurgen Habermas's Public Sphere, where the internet should be a communicative space to create public rationality in achieving Deliberative Democracy. The research method involves a mix of literature review and quantitative descriptive methods. The SWOT analysis is used to assess the strengths, weaknesses, opportunities, and threats of new media. The study's results indicate that the strength lies in the quantity and duration of internet users that can be maximized. Weaknesses include the quality and characteristics of users. There is potential in terms of infrastructure, reach, and proximity. Threats include both manifest issues such as hoaxes and incitement, as well as latent issues such as the failure to accommodate the needs of society.